(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
In this work, we analyze the DN Constant (Del Gaudio-Nardelli Constant). We will describe the possible mathematical connections with Ramanujan’s Recurring Numbers, some parameters of Number Theory and String Theory